La Sierra de A Capelada (A Coruña), un interesante enclave liquénico - Sánchez Biezma, María José; Carballal Durán, Regina (Lazaroa, 2000)
Sánchez-Biezma, M. J. & Carballal, R. The Sierra de A Capelada (A Coruña), an interesting lichenological area. Lazaroa 21: 7-11 (2001). This study highlights the biogeographic importance of the Sierra de A Capelada lichenological site due to the presence among the rich saxicolous flora of some species with North Atlantic or Mediterranean distributions, as well as others from more specific localities. tingente de 218 táxones saxícolas caracterizados por